2018
DOI: 10.3892/etm.2018.6514
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the κ1 opioid receptor promoter in Chinese heroin and methamphetamine addicts

Abstract: Heroin and methamphetamine (METH) addiction continues to be a major social, economic and therapeutic problem worldwide. The opioid pathway may mediate the effects of addictive drugs. However, the potential correlation between the κ1 opioid receptor (OPRK1) and drug addiction has not yet been characterized. The aim of the present study was to investigate the potential association between methylation of the OPRK1 promoter and substance abuse. Bisulfite pyrosequencing technology was used to determine the levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…23 However, no significant association was found between neither age nor gender of the heroin users and, κ1 opioid receptor (OPRK1) gene methylation, which is in line with the results of the present study regarding the NISCH gene. 24 Moreover, no association was found between the duration of opium consumption and gene methylation status. Although it was not statistically significant, the hypermethylation of the studied genes in opium addicted persons can be assumed as a long-term effect since the average time of opium consumption was about 97 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, no significant association was found between neither age nor gender of the heroin users and, κ1 opioid receptor (OPRK1) gene methylation, which is in line with the results of the present study regarding the NISCH gene. 24 Moreover, no association was found between the duration of opium consumption and gene methylation status. Although it was not statistically significant, the hypermethylation of the studied genes in opium addicted persons can be assumed as a long-term effect since the average time of opium consumption was about 97 months.…”
Section: Discussionmentioning
confidence: 99%
“…25 Ji et al found a significant correlation between the frequency of heroin use and methylation of OPRK1 gene promoter among male cases. 24 Two methylated single-nucleotide polymorphism (SNP)-CpG sites were identified in the Dopamine Receptor D1 (DRD1) gene among heroin abusers. However, the correlations between the methylation of the aforementioned sites and the frequency, amount, and duration of heroin use were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent clinical study showed that methamphetamine-induced changes in long interspersed element-1 methylation are associated with methamphetamine-induced paranoia and therefore may partially explain the pathophysiology of this type of psychosis ( Kalayasiri et al, 2019 ). Previous preclinical study reported that κ1 opioid receptor (OPRK1) promoter methylation was significantly correlated with the length and frequency of drug use in Chinese male heroin addicts ( Ji et al, 2018 ). Xu et al (2016) demonstrated that methylation level of one CpG sites in brain derived neurotrophic factor (BDNF) promoter was significantly associated with addictive phenotypes of heroin-dependent individuals, including tension-anxiety, anger-hostility, fatigue-inertia, and depression-dejection.…”
Section: Introductionmentioning
confidence: 99%